Effect of death of Diana, princess of Wales on suicide and deliberate self-harm. - Hawton, K; Harriss, L; Simkin, S; Juszczak, E; Appleby, L; McDonnell, R; Amos, T; Kiernan, K; Parrott, H (2000)
BACKGROUND: The death of the Princess of Wales in 1997 was followed by widespread public mourning. Such major events may influence suicidal behaviour. AIMS: To assess the impact of the Princess's death on suicide and deliberate self-harm (DSH). METHOD: Analysis, using Poisson regression, of the number of suicides and open verdicts ('suicides') in England and Wales following the Princess's death compared to the 3 months beforehand, and the equivalent periods in 1992-1996. Similar analysis on DSH presentations to a general hospital. RESULTS: Suicides increased during the month following the Princess's funeral (+17.4%). This was particularly marked in females (+33.7%), especially those aged 25-44 years (+45.1%). Suicides did not fall in the week between the death and the funeral. Presentations for DSH increased significantly during the week following the death (+44.3%), especially in females (+65.1%). Examination of case notes suggested that the influence of the death was largely through amplification of personal losses or exacerbation of existing distress. CONCLUSIONS: The death of a major public figure can influence rates of suicidal behaviour. For DSH, the impact may be immediate, but for suicide it may be delayed.